The association between urine neutrophil gelatinase-associated lipocalin and UTI in people with neurogenic lower urinary tract dysfunction - Forster, Catherine S.; Lamanna, Olivia K.; Rounds, Amanda; Sprague, Bruce M.; Ljungberg, Inger; Groah, Suzanne L. (Spinal cord, 2021)
Study design Secondary analysis of urine samples collected from a prospective within-subject clinical trial. Objectives Describe the baseline variation in urine neutrophil gelatinase-associated lipocalin (uNGAL) levels in adults with neurogenic lower urinary tract dysfunction (NLUTD) and determine if uNGAL levels vary according to likelihood of having a UTI. Setting Greater Washington D.C. region. Methods Urine samples were collected from a cohort of adults with NLUTD from a clinical trial. Samples were divided into groups of “Not UTI”, “Unlikely UTI”, and “Likely UTI” based on symptoms and urine culture results. uNGAL was compared between groups using Kruskal–Wallis and post hoc Dunn’s test. Mixed effects logistic model was used to assess the association of uNGAL and Likely UTI. Results Twenty-seven participants provided a total of 104 samples. uNGAL levels were lowest for the No UTI group ( n = 29; 37 ng/ml interquartile range (IQR) (15, 71)), intermediate for the Unlikely UTI group ( n = 67; 95 ng/ml IQR (37, 161)) and highest for the Likely UTI group ( n = 8; 187 ng/ml IQR(146, 224)). uNGAL levels were higher in those with Likely UTI compared to both Unlikely UTI ( p < 0.05) and No UTI ( p < 0.01). uNGAL had an association with Likely UTI (OR 1.01, 95% CI (1.00–1.02), p = 0.049). Conclusions Adults with NLUTD have notable variation in uNGAL levels in the absence of symptoms potentially due to UTI. uNGAL levels are higher in those who are likely to have UTI have higher uNGAL levels compared to those with non-specific symptoms and/or less growth on urine culture. uNGAL may have utility as a marker of UTI in people with NLUTD. Sponsorship Patient-Centered Outcomes Research Institute (PCORI) funded this work. Bioporto provided partial salary support for SLG, IL, and OKL. NGAL ELISAs were provided by Bioporto in kind.